Working knowledge: the new vocationalism and higher education - Symes, Colin; McIntyre, John (Open University Press / Society for Research into Higher Education, 2002)
Universities are undergoing a series of profound changes. One of the more pronounced of these involves the partnerships that are now being formed between business enterprises and higher education. The emergence of these partnerships has much to do with the changing economy, which is increasingly based around knowledge and information - the traditional stock-in-trade of the university. Knowledge capitalism has given a renewed impetus to higher education. One expression of this is work-based learning, which challenges the scope and site of the university curriculum. This book analyses this development from a number of perspectives: critical, historical, philosophical, sociological and pedagogical. Its various contributors argue that work-based approaches contain much that is challenging to the university, and also much that could help to create new frameworks of learning and new roles for academics. Working Knowledge offers a comprehensive examination of the new vocationalism in higher education.